2007
DOI: 10.1111/j.1460-9568.2007.05757.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the norepinephrine transporter by α‐synuclein‐mediated interactions with microtubules

Abstract: alpha-Synuclein (alpha-Syn) regulates catecholaminergic neurotransmission. We demonstrate that alpha-Syn regulates the activity and surface expression of the norepinephrine transporter (NET), depending on its expression levels. In cells co-transfected with NET and low amounts of alpha-Syn, NET activity and cell surface expression were increased and protein interactions with alpha-Syn decreased, compared with cells transfected with NET alone. Converse effects were observed at higher levels of alpha-Syn expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 64 publications
6
63
0
Order By: Relevance
“…␣-Synuclein. DAT, NET, and SERT have all been found to interact with ␣-synuclein, a presynaptic protein that is implicated in the pathogenesis of Parkinson's disease Wersinger and Sidhu, 2005;Wersinger et al, 2006a,b;Jeannotte and Sidhu, 2007). Coexpression studies revealed that ␣-synuclein modulated transporter activity by regulating cell surface expression; however, it is not clear whether the regulation is stimulatory or inhibitory.…”
Section: G Protein-protein Interactionsmentioning
confidence: 99%
“…␣-Synuclein. DAT, NET, and SERT have all been found to interact with ␣-synuclein, a presynaptic protein that is implicated in the pathogenesis of Parkinson's disease Wersinger and Sidhu, 2005;Wersinger et al, 2006a,b;Jeannotte and Sidhu, 2007). Coexpression studies revealed that ␣-synuclein modulated transporter activity by regulating cell surface expression; however, it is not clear whether the regulation is stimulatory or inhibitory.…”
Section: G Protein-protein Interactionsmentioning
confidence: 99%
“…Synaptosomes were prepared from freshly killed animals as described previously (Jeannotte and Sidhu, 2007). Briefly, the tissue was suspended in 10% w/v synaptosome homogenizing buffer, homogenized on ice, and centrifuged at 500 g for 10 min at 41C.…”
Section: Synaptosome Preparationmentioning
confidence: 99%
“…Uptake assays were performed on intact and adherent transiently transfected cells or freshly prepared synaptoa-and c-Synuclein modulation by desipramine in depression AM Jeannotte et al somes as described previously (Jeannotte and Sidhu, 2007). Briefly, uptake into cells was performed using room temperature uptake buffer (Krebs-Ringer-Hepes) and a final concentration of 20 nM [ 3 H]-NE.…”
Section: [ 3 H]-ne Uptake Assays and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations